Tax for unmarried and childless persons (bachelor tax) in a historical perspective and possibilities for its establishment in modern times - Tsvetanova, Marina (Law Journal of New Bulgarian University, 2022)
The article examines the establishment of the tax for unmarried and childless persons (bachelor tax) and its historical development during the four Bulgarian constitutions. The problems of the legislative process are being explored, as well as those of the compliance of the bachelor tax with the constitutional and tax provisions, with the principles and objectives of taxation, the fundamental rights and constitutional principles. The article discusses the possibility for the establishment of this tax in modern times.